Facing The Qibla When Defecating (Mukhtalif Al-?adith Study) - Abdurrohman, Abdurrohman; Takwallo, Takwallo; Johanna, Anne; Avinash, Buschhaus (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
Starting from the issue of facing the Qibla when defecating, where there are two different hadith editors in their views on the subject. There are hadiths that allow defecation by facing the Qibla, but there are also hadiths that notaben forbid it in one book at a time (kitab al-Bukh?r?). Judging from the two hadiths, it clearly seems to be contradictory regarding facing the Qibla when defecating. With this the author is interested in conducting research with the formulation of the problem. 1. How to understand the hadith about the prohibition and acquisition of defecation facing the Qibla. 2. How to resolve the meaning of the hadith that contradictions between prohibition and the ability to face the qibla when defecating. The study that the author will conduct in this study is to solve two conflicting hadiths using the study of Mukhtalif al-? adith science. The method used by the author is the qualitative method or (library resarch), with reference to the book of hadith, namely: ?a?i? al-Bukh?r? as well as applying the mukhtalif study of ?ad?th in completing two contradictory hadiths about the prohibition and ability to face the Qibla when defecating. Based on the results of research on the hadith contradiction about facing the Qibla when defecating, in resolving the contradiction, namely by compromising (al-jam'u). In a sense, it is not allowed to face the Qibla when defecating if it is done in the open or field. And it is allowed if it is in a building. So the two hadiths are both used, without having to delete or silence one of them.